Modern Plant Breeding For Sustainable Agriculture: A Review - Selvia Dewi Pohan; Noraziyah Abd Aziz Shamsudin; Jamsari Jamsari; Tika Runifah (Department of Crop Science, Faculty of Agriculture, Andalas University, 2021)
More foods are required to fulfill human need. The limitation of the farming area is leading to intensification system in crop cultivation, so the use of chemical properties and environmental destruction cannot be denied. However, this industrial practice in the crop system has caused many adverse effects on ecological balance and human health. Many severe impacts of industrial agriculture practices have been reported, including soil erosion, groundwater contamination, loss of productivity, depletion of fossil resources, air pollution, new threats to human health and safety. Many experts agreed that sustainable agriculture seems to be an effective way to solve these issues. Modern plant breeding is now a popular approach to provide superior crop cultivars that can minimize adverse effects of agriculture practices because humans can recognize and manipulated genes through this method. Recently, the application of molecular markers in plant breeding selection has been brought enthusiasm for plant breeders. Marker-assisted selection (MAS) has been evidenced to be a beneficial technique in plant breeding. Through this approach, the selection process of parents and progenies in the breeding process could be more efficient. Plant breeding is influential in crop production achievement because this effort is connected with the adaptability and stability of the varieties in many different environmental circumstances. Plant breeding also focuses on agriculture sustainability due to its effort to produces durable disease resistance, abiotic stress tolerance, nutrients, and water-use efficiency.